A CHAPTER REVIEW: SELECTING LANGUAGE FOR MATERIALS WRITING: (The Routledge Handbook of Materials Development for Language Teaching-Routledge) - Zulkifli Surahmat; Ahmed Sardi; Muh. Firmansyah JN (Al-Irsyad: Journal of Education Science, 2023)
This chapter review will discuss the current topic in chapter 6 from a book entitled “The Routledge Handbook of Materials Development for Language Teaching-Routledge” Edited by Julie Norton and Heather Buchanan. The selection of grammar and the selection of vocabulary for the creation of English Language Teaching (ELT) course books have been the two main topics of this chapter. Given the homogeneity of many published materials, it is simple to believe that the subject of "what" to teach to EFL students has long since been resolved. Instead, research should concentrate on the "how" of ELT, or pedagogy, in particular, and how this might be reflected in materials design. This assumption, however, would be inaccurate for two reasons. First of all, especially in the case of language, we have inherited a consensus whose development has generally taken place outside of the purview of empirical study and has been somewhat "piecemeal." Second, a variety of fiercely disputed aspects of contemporary research, including initiatives like the English Profile, imply that it might be time to review and revise the "what" of ELT.